SACROCOCCYGEAL HYDATID CYST - ANOTHER ENTITY IN THE DIFFERENTIAL-DIAGNOSIS OF SACROCOCCYGEAL CHORDOMA - CASE-REPORT - (:unkn) unknown (STOCKTON PRESS, 1993)
A case of hydatid disease of the sacrum with severe neurological symptoms, which was misdiagnosed preoperatively as a chordoma, is presented. The patient had significant improvement of the neurological symptoms after evacuation of the cyst. Sacral hydatid cysts must be considered in the differential diagnosis of sacrococcygeal chordoma.
Keywords: HYDATID CYST; SACRUM; CHORDOMA